Weakening of antipodes affects the Earth's climate - Campoblanco Díaz, Honorio (1999)
The opposite ends of the plasma state matter are present on the earth's surface , as immense anteladamente thermometers indicating periods when the weather is in balance or imbalance. One such extreme is made glaciers provided a powerful potential energy aimed at maintaining order, strength and energy conservation structures and flows, the other end is the fire of volcanoes with their powerful kinetic energy , ready to be transformed into other forms energy , both events are the " Antipodes energy " from matter to plasma state . During the Pleistocene and periods when glaciers dominated large tracts of land , there was evolution or involution of certain species as well as man's ancestors : the Ramapithecus , Australopithecus , Homo Habilis , Homo Erectus , Neandhertal and Homo Sapiens , products cataclysms and abrupt climate changes on the Earth's surface , likewise, increase the heat to allow the development of life nuanced major disasters and climatic changes, then an immense variety of flowering (including giants) species within the spectrum of geologic time . By looking at the earth as a whole , we see that it is governed by different types of " energy antipodes " so that almost the entire Western Hemisphere is occupied by the Pacific Ocean where there is predominance of kinetic flows represented by earthquakes , earthquakes , tsunamis , waves , and phenomena of volcanism " the tectonic Child " favored by the heat and energy from within the earth, and in the Eastern Hemisphere continents consisting of : Europe, Africa , Asia and India dominate friajes , droughts, hurricanes product domain "La Niña" . Similarly, in the North Pole the Arctic Ocean ( cold water mass ) is located, in contrast to the South pole occupied by the continent of Antarctica , whose energy relations allow rotational kinetic equilibrium and as such, the presence of favorable climates on earth . This distribution allows us to understand the climate " is the result of a state of balance or imbalance of different energy antipodes operating on the biosphere ."